Business Process Oriented Knowledge Management System Design (Case Study Development Center of Metrological Human Resources, Ministry of Trade Republic of Indonesia) - Febriantoro, Wicaksono; Surendro, Kridanto (The Asian Journal of Technology Management (AJTM), 2015)
Abstract. The aim of this  study  is to  design a business process oriented Knowledge Management System (KMS) in government training institutions using knowledge modeling methods  and  knowledge  infrastructure  process  design  of  Strohmaier. Lecturer  (WI) business process is the main case study for this research. The preliminary identification and analysis showed that 7 of 10 business processes have not been fully identified in terms of their knowledge  processes. Further analysis showed that  in  general,  all  business processes have not been optimized yet to fulfill all the components of knowledge creation to knowledge application. The results of the completed knowledge process design showed that there are 53 stages of the process (there are new additional 19 stages of the process). The new processes are largely on the knowledge transfer and knowledge application that have been defined.  In  addition,  KMS  architecture  and  IT  tools  as  supporting  knowledge infrastructure designs  are  defined.  The  IT  tools  are  expected  to  support  two  knowledge process strategies :the codification strategy with the  supporting  IT  Tools : content  management  system ,  information  retrieval  system,  expert  locator  and  the personalization  strategy with  the  supporting  IT  Tools such as community of practice tool, virtual work space application and discussion group based application.Keywords: business processes, knowledge process, knowledge management system, knowledge infrastructure, IT Tools